A Holistic Career Framework: Integrating Bourdieu and career theory. (April 2022) - Gander, Michelle
This study sets out to argue for the interplay between structure and agency to create a deeper understanding of careers. Using Bourdieu's Theory of Practice as an integrative framework for career theory, this study sets out to answer two questions: (1) does the concept of a Holistic Career Framework add value to the career debate by placing emphasis on both agency and structure? (2) does a Holistic Career Framework help link theory with practice? One hundred and thirty-nine career stories from university professional staff were analysed using a narrative approach, coded and thematically analysed for overarching patterns. The Holistic Career Framework was used as a lens to further understand individual career needs and decisions. By analysing the career stories of university professional staff, and understanding the context in which they operate, a deeper understanding of career behaviour and decision-making is provided.